Genomic analysis and chitinase characterization of Vibrio harveyi WXL538: insight into its adaptation to the marine environment - Ran, Lingman; Wang, Xiaolei; He, Xinxin; Guo, Ruihong; Wu, Yanhong; Zhang, Pingping; Zhang, Xiao-Hua (Frontiers in Microbiology, 2023)
Chitin, the most abundant bio-polymer in seawater, may be utilized by various microorganisms as a carbon source. Vibrios have been regarded as one of the main groups of chitin consumers in the marine carbon cycle and chitinase producers. The organisms are widely distributed in the aquatic environment. However, the co-working mechanism between their chitinases and whether the chitinase’s diversity contributes to the adaption to the environment needs to be further elucidated. Here, we obtained a chitinolytic strain Vibrio harveyi WXL538 with eight putative chitinase-coding genes. Five of the genes, i.e., Chi4733, Chi540, Chi4668, Chi5174 and Chi4963, were overexpressed and validated, in which Chi4668 (He et al., 2020), Chi4733 and Chi540 were purified and characterized. Endo-chitinase Chi4733 degraded colloidal chitin to produce (GlcNAc)2 and minor (GlcNAc)3. The enzymatic activity of Chi4733 was 175.5 U mg-1 and Kcat/Km was 54.9 s-1M-1. Chi4733 had its maximum activity at 50℃ and pH 4-6, activated by Sr2+, Co2+, Ca2+ and Mg2+ and inhibited by Al3+, Zn2+, Cu2+, Ni2+ and SDS. Exo-chitinase Chi540 degraded colloidal chitin to (GlcNAc)2. The enzymatic activity of Chi540 was 134.5 U mg-1 and Kcat/Km was 54.9 s-1M-1. Chi540 had its maximum activity at 60℃ and pH 6-8, was activated by Sr2+, Ca2+ and Mg2+ but inhibited by K+, Ba2+, Zn2+, Cu2+, Ni2+, SDS and urea. Whole genome analysis of V. harveyi WXL538 and characterization of its chitinase can provide a better understanding of its adaptability to the changing marine environment.